Politics of memory for a New Era? Mainland Chinese historical memory, nationalism, and their impact on Chinese international behaviour - Bachulska, Alicja (Asia in World Politics: Past, Present, and Future, 2021)
Overall, the subject has remained relatively understudied. In this context, this paper presents a broader picture of the importance of the topic as such. It does not attempt to present a complete picture of the role of historical memory in Chinese foreign policy. Instead, it identifies the main points of reference that should be treated as the invitation for further research. It also highlights certain new developments that might suggest what to expecct in the future. However, from the perspective of international politics, scientists have been somehow reluctant to study the impact of historical memory on states’ behaviour. In the academic world of IR, dominated by realism, immeasurable factors like identity or culture, have been considered largely insignificant in shaping international politics. If one defines power as one state’s ability to control a given sphere either militarily or economically, intangible factors somehow “naturally” get sidelined. Nevertheless, given the worldwide resurgence of nationalism as a political force shaping international relations and the impossibility of explaining it with purely realist means, some observers have turned towards a re-examination of alternative or subsidiary explanations of factors influencing states’ international behaviour. Northeast Asia accounts for one of the most well-developed regions with the world’s three largest economic powers. However, as former South Korean President Park Geun-hye described, it also constitutes a “paradox.” On one hand, states are able to successfully cooperate on the economic basis. On the other hand, there are a number of obstacles, involving primarily unresolved historical issues and security concerns, that impede further regional collaboration. The aim of the article is to analyse the process of regional integration in Northeast Asia, with particular focus on Japan – Republic of Korea relations, through the lenses of neo-functionalism. The essay seeks to determine whether this approach could lead to increasing transnational ties in the region and ultimately improve international relations on bilateral and multilateral basis. Neo-functional theory of regional integration has been mostly applied to research on the European integration process. Consequently, there have been few attempts of testing its assumptions in other regions. Nevertheless, there seems to be substantial evidence to perceive neo-functionalism as a promising theoretical approach beyond Europe. Since neo-functionalists place supranational, transnational and sub-national actors at the centre of the analysis, the article, apart from the economic dimension, will elaborate on the potential of existing international structure, namely the Trilateral Cooperation Secretariat.